Edukasi Pengelolaan Sampah dan Literasi Digital Bank Sampah sebagai Upaya Peningkatan Nilai Ekonomi Masyarakat - Prio Kustanto; Mayadi; Ahmad Fathurrozi (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2026)
Waste management remains one of the major challenges in urban areas such as Bekasi City, where the volume of household waste continues to increase while most residents still regard waste as having no economic value. In response, Yayasan Cahaya Insan Sejahtera organized a community education program themed